FIRM HETEROGENEITY AND EXPORT ACTIVITY OF EUROPEAN FIRMS: A QUANTILE ANALYSIS - Orts, Vicente; Martí, Josep (Revista de Economía Mundial, 2018)
This paper examines the extent to which firms’ characteristics are related to export activity behaviour. Using a dataset comprised of harmonized and detailed firm-level data from six European countries (Austria, France, Germany, Italy, Spain and United Kingdom) for the period 2007-2009 (EFIGE dataset), we analyse the effects of firms’ characteristics on two different measures of export activity: export intensity and market scope. Firstly, we estimate OLS regressions to analyse this relationship. Our empirical results show that there is a positive relationship between firms’ characteristics and export activity. Secondly, quantile regressions are performed in order to observe whether there are any heterogeneous effects along the conditional distribution of the two measures of export activity. The quantile regressions reveal the existence of heterogeneous effects and nonlinearities among firms’ characteristics and both export intensity and market scope. Moreover, the quantile analysis also shows that, for some cases, the effects of firms’ characteristics on export intensity and market scope differ greatly.